HUBUNGAN DUKUNGAN EMOSIONAL PASANGAN HIDUP DENGAN PEMENUHAN ACTIVITY DAILY LIVING (ADL) LANSIA DI HUTAN LINDUNG WILAYAH KERJA PUSKESMAS MUARABULIAN - Yade kurnia sari Yade; Yulia M Nur; Andeska Fitri Deska (STIKes Al-Insyirah Pekanbaru, 2022)
Eldery generally have a dependency in performing daily activities. Some of the factors that influence such as age, cognitive function, disease, physical health factors, psychological one of them is emotional support in this case from spouse. The purpose of this study to determine the The Correlation between Emotional Support at from Spouse and the Fulfillment of Activity Daily Living (ADL) on The Elderly at West Ungaransubdistrict.Research using corelative analytic method with cross sectional approach.The study population elderly who have a spouse. Sampling technique was purposive sampling, with sample number 61 elderly who have a spouse. Collecting data used questionnaires emotional support and Barthel index. Data analysis using chi-quare.Regencyobtain emotional support in high category, as many as 25 respondents (41.0%). Activity Daily Living (ADL) in independent category ofas many as 38 respondents (62.3%). The Correlation Between Emotional Support At From Spouse And The Fulfillment Of Activity Daily Living (ADL) On The Elderly At with a p value of 0.000.Based on the results of the study are expected spouse of elderly always provide emotional support in the form of affection, empathy and concern that elderly motivated to perform daily activities independently.